No-reference video quality assessment model based on artifact metrics for digital transmission applications - Silva, Alexandre Fieno da (2017)
Tese (doutorado)—Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2017.